Propeller-Pendulum for Nonlinear UAVs Control - Huba, Tomáš; Malatinec, Tomáš; Huba, Mikuláš (International Journal of Online and Biomedical Engineering (iJOE), 2013)
This paper presents basic information about new experiment and about the wrapped-around learning objects for nonlinear control and other relevant topics from the mechatronics area. Its primary aim is to motivate students within the framework of the â??learning by playingâ?, â??learning by discoveringâ?, or through â??experiential learningâ? approaches to drag them to study this highly sophisticated stuff. The experiment may deal with simple but challenging positional or velocity control tasks requiring knowledge of basic physical principals of mechanics and of the associated mathematical apparatus of nonlinear differential equations. Furthermore, it is also used to master related measurement and communication problems, to carry out embedded control design and programming of embedded devices. Finally, it is also useful and illustrative in comparing traditional control methods that may be confronted towards the latest development in several areas of modern control theory.